PENGARUH MEDIA PEMBELAJARAN INTERAKTIF GENIALLY TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS IV DI SEKOLAH DASA - Tiara Aprilyani; Asep Usamah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The writing of this research is motivated by the less than optimal learning outcomes of fourth grade students, this study aims to determine how the use of interactive learning media genially affects student learning outcomes in science learning in fourth grade elementary school before and after the use of learning media genially. This study uses a quantitative method, using the Quasi Experiment type with a Nonequivalent Control Design design. With the sampling technique in this study using a purposive sampling technique. In this study involved 38 students, fourth grade SD Negeri 1 Cipedes. The sample studied amounted to 38 in class IV A 19 students and IV B 19 students. With data collection techniques carried out by interviews, observations, tests and documentation. The results of the analysis show that the average value increased from 66 to 84. The results of the hypothesis test with the Independent Samples T Test strengthen the results of the study by obtaining a Sig (2-tailed) value of 0.000 below 0.05. So Ho is rejected Ha is accepted. So it can be concluded that the results of this study are that this Genially learning media has been proven to have an influence on improving student learning outcomes in science learning in grade IV of elementary school.